Laplace Transforms Part II
Laplace Transforms Part II
Laplace Transforms Part II
Part-II
Pradeep Boggarapu
December 1, 2022
which is true for all large values of p, as the function f (x) is of exponential
order. Thus
L[f 0 (x)] = pL[f (x)] − f (0).
Now we will see that how the Laplace transform will be used to solve the
initial value problem (0.1), let us apply Laplace transform on both sides of
(0.1):
L[y 00 ] + aL[y 0 ] + bL[y ] = L[f (x)]. (0.3)
Here we assume that the function f (x) is piecewise continuous and of
exponential order. Once this assumption is made, then it can be shown
(we omit the proof) that y , y 0 and y 00 necessarly have the same
properties, so they have Laplace transforms.
L[3x 2 ] + (p + 1) · 0 + 1 3(2!/p 3 ) + 1 6 + p3
L[y ] = = = .
p2 + 1 · p + 0 p2 + p p 4 (1 + p)
Note that inverse Laplace transform of given F (p) may or may not exists,
if it exists, it may not be unique but continuous inverse Laplace transform
is unique.
Pradeep Boggarapu Laplace Transforms December 1, 2022 5 / 24
Example-2: Find the inverse Laplace transforms of
p 2
(a) p 2 +4
(b) p 2 +4
1 6+p 3
(c) pn (d) p 4 (1+p)
.
Sol.
−1 p p
(a). L 2
= cos 2x; since L[cos 2x] = 2 .
p +4 p +4
2 2
(b). L−1 = sin 2x; since L[sin 2x] = 2 .
p2 + 4 p +4
x n−1
−1 1 n!
(c). L n
= ; since L[x n ] = n+1 .
p (n − 1)! p
6 + p3
−1 −1 6 6 6 5 5
L =L − + − +
p 4 (1 + p) p4 p3 p2 p p + 1
−1 6 −1 6 −1 6 −1 5 −1 5
=L −L +L −L +L
p4 p3 p2 p p+1
= x 3 − 3x 2 + 6x − 5 + 5e −x .
Since
Z ∞
ax
L[e f (x)] = e −px e ax f (x) dx
Z0 ∞
= e −(p−a)x f (x) dx = F (p − a).
0
The formula can be used to find the transforms of product of the form
e ax f (x) when F (p) = L[f (x)] is known and also to find the inverse
transforms of functions of the form F (p + a) when L−1 [F (p)] = f (x) is
known.
−1 6 −2x −1 6
(a). L =e L = e −2x sin 3x.
(p + 2)2 + 9 p2 + 9
−1 12 −3x −1 12
(b). L =e L = 2x 3 e −3x .
(p + 3)4 p4
(c).
p+3 (p + 1) + 2 −x −1 p + 2
L−1 2 = L−1 = e L
p + 2p + 5 (p + 1)2 + 4 p2 + 4
p 2
= e −x L−1 2 + 2 = e −x (cos 2x + sin 2x).
p +4 p +4
d2
2
a − 3p 2
2 d 2ap
L[x sin ax] = 2 L[sin ax] = − = −2a
dp dp (p 2 + a2 )2 (p 2 + a2 )3
Exampl-2: We have shown that L[x −1/2 ] = π/p, so
p
r
1/2 −1/2 d p 1 π
L[x ] = L[x(x )] = − π/p = .
dp 2p p
d2 p
r
3/2 2 −1/2
3 π
L[x ] = L[x (x )] = 2 π/p = 2 .
dp 4p p
And hence Z ∞ Z ∞
f (x)
dx = F (p) dp (0.10)
0 x 0
which is valid whenever the integral on the left exists.
f (x)
To prove this, we let G (p) = L , as F 0 (p) = L[−xf (x)] we get that
x
dG f (x)
=L −x = L[−f (x)] = −F (p)
dp x
2 Show that
p 2 − a2
L[x cos ax] = ,
(p 2 + a2 )2
use theis result to fine L−1 1/(p 2 + a2 )2 .
1
y (0) = y 0 (0) = 0 has y (x) = f (t) sin a(x − t) dt as its solution.
a 0
Pradeep Boggarapu Laplace Transforms December 1, 2022 18 / 24
Now we will see that how we use the Laplace transforms to solve the
second order linear differential equations of the form:
dY dY 3Y
Or [−p 2 − 3p + 4] − [3p + 12]Y = 0 which implies = . Now
dp Z Z dp 1 −p
dY dp
we separate the variables and integrate, = then we get
Y 1−p
C
log Y = −3 log (p − 1) + c or L[y ] = Y = (p−1) 3 . Apply inverse Laplace
2
transform y (x) = L−1 (p−1)
C
3 = C x2 e x .
Pradeep Boggarapu Laplace Transforms December 1, 2022 20 / 24
Problems
1 Solve each of the following differential equations:
or
L[f (x)]
L[y (x)] =
1 + L[k(x)]